ASAS-ASAS PENGEMBANGAN KURIKULUM LEMBAGA PENDIDIKAN ISLAM - Andi Nirmayanthi; Aguswati; Siti Azisah, Muh Wayong (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Curriculum development in Islamic educational institutions is a crucial process to ensure that education aligns with the principles of Islam while meeting modern educational needs. This article discusses the principles of curriculum development in the context of Islamic educational institutions. These principles include theological principles, which refer to the teachings of Islam derived from the Quran and Sunnah; philosophical principles, encompassing the philosophical principles underlying Islamic education; psychological principles, involving learning theories and the psychological development of students; socio-cultural principles, considering the cultural and social context of Islamic society; and scientific and technological principles, utilizing science and technology in learning. By adhering to these principles, Islamic educational institutions can develop a curriculum that is holistic, values-oriented, and relevant to contemporary demands, preparing students to become beneficial individuals for society and the Islamic community at large.